Potato Park - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The Potato Park, located in Pisaq in the Sacred Valley of Peru, is one of the few in-situ conservation initiatives in the world where the local people are managing and protecting local genetic resources and traditional knowledge about their health, food, and agriculture. About 600 varieties of native potatoes grow in the Park, most of them unique to this habitat. Six Quechua communities live in the Park.